The application of multivariate classification method by reference points to determine the degree of spontaneous combustion of coal on the example of the Raspadskaya mine in Kuzbass - F. A. Golynskaya; O. C. Smirnova; R. A. Nikonov (Известия высших учебных заведений: Геология и разведка)
The objective of the research was to use the data about coal seam, obtained at the stage of exploration, to predict spontaneous combustion of coal. As a result of studying the geological structure of coal seams, physical-chemical research and analysis of statistical data on the spontaneous combustion of coals, geological factors of spontaneous combustion of coal and the boundary values of their parameters varying degrees of danger of spontaneous combustion for a number of basins and deposits were established. The basis of the authors’ methodology is based on ranking the data model and on the idea to classify this data by «proximity» to the reference groups of observations. The transition from the original data of the coal seam to rank scale was carried out using standards (boundary values) of levels of danger of spontaneous combustion of coal. The obtained data were used to construct maps of the prediction of spontaneous combustion of coal fields in «Raspadskaya» mine in Kuzbass.